RIGHTS OF BANKRUPT DEBTORS IN THE MANAGEMENT AND SETTLEMENT PROCESS IN ACCORDANCE WITH LAW NUMBER 37 OF 2004 CONCERNING BANKRUPTCY AND PKPU - Muhammad Nurrohim; Zetria Erma (PENA LAW: International Journal of Law, 2023)
The debtor's rights in the process of settling bankruptcy assets are very weak, where the debtor will lose his rights to control and manage his assets which are included in bankruptcy assets as stipulated in Article 24 Paragraph (1) of the Bankruptcy Law. However, in the event that the debtor is declared bankrupt, the law gives the debtor the right to submit a reconciliation plan, submit a postponement of debt payment obligations and submit an appeal and review, all of which are efforts to protect the rights of the debtor. In the process of settling bankruptcy assets, the legal protection for debtors' rights is quite weak. Because since the pronouncement of the bankruptcy declaration decision by the court, the debtor will lose the right to manage his assets which are included as bankruptcy assets. As a result, the debtor is no longer able to legally act on his assets that are included in the bankruptcy estate, in this case the management of bankruptcy assets becomes the authority of the curator and/or BHP.